2015
DOI: 10.1590/s0102-053620150000300004
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade e tolerância à queima-das-folhas de diferentes genótipos de cenoura de verão

Abstract: Productivity and tolerance to the leaf blight disease of hybrid and open-pollinated carrot cultivars

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Regarding the two open pollination cultivars, Carvalho et al (2015), measuring MRM at 100 DAS, found superior yield of commercial roots from BRS Planalto over Brasília, with values of 25.81 and 16.06 t ha -1 , respectively. Likewise, Carvalho et al (2017), in the evaluation in 20 environments, found an average MRM value of 34.54 t ha -1 for 'Brasília' and 35.95 t ha -1 for BRS Planalto.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Regarding the two open pollination cultivars, Carvalho et al (2015), measuring MRM at 100 DAS, found superior yield of commercial roots from BRS Planalto over Brasília, with values of 25.81 and 16.06 t ha -1 , respectively. Likewise, Carvalho et al (2017), in the evaluation in 20 environments, found an average MRM value of 34.54 t ha -1 for 'Brasília' and 35.95 t ha -1 for BRS Planalto.…”
Section: Resultsmentioning
confidence: 98%
“…There were no differences between the three cultivars for nonmarketable root mass (NRM), showing that although the hybrid HX 4098 had lower TRM than the open-pollinated cultivars, it presented MRM equivalent to BRS Planalto by the lowest NRM. As emphasized by Carvalho et al (2015) and Pereira et al (2015), the heterosis of carrot hybrids is due to the higher proportion of marketable roots, as these tend to have more uniform roots than open pollinated cultivars.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In carrot primary growth, which occurs in the first 45 days after sowing, root length is highly influenced by the environment (Carvalho et al 2015). In this period, paper mulching promoted the best condition for root elongation, due to the transmission and reflection of most of the solar radiation incident on the leaf and soil (You et al, 2021), while the treatment with plastic mulching had an adverse effect, caused by the absorption of much of the incident radiation from the crop and soil.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary growth, which occurs from 45 days until close to harvest (±100 days for summer carrots), is marked by the expansion of the diameter (Carvalho et al 2015). When applying deficit irrigation depths, smaller root diameters were obtained, as small changes in cell turgor during the cell growth process reflect a decline in cell expansion and growth (Jones, 2010;Taiz et al, 2017).…”
Section: Discussionmentioning
confidence: 99%